As vivências dos trabalhadores de um shopping center em relação ao seu trabalho: uma abordagem psicodinâmica - Tomazini, Talita (2009)
The present study is the result of a research accomplished in an organization that deals in the leisure and entertainment area: a shopping center. It is a study case with descriptive and exploratory characteristics and its general aim was to investigate how the Shopping Center workers live their working days. The specific objectives of this research consist of: analyzing the experiences of the shopping center workers in relation with the organization of their work, their working conditions, the work relations, the pleasure and suffering experiences and the strategies of coping, both individual and collective used by them to deal with their work suffering. The theoretical basis for this research was a psychodynamic work approach. To collect the data we used individual semi-structured interviews with twenty workers divided in two groups (six of them worked in the administrative area and fourteen dealt with the operational area). After the transcription, the interviews were analyzed according to a speech graphic analysis. The data indicated that the work organization, the working conditions and the work relations have similar characteristics when compared to other organizations. They were put together in a specific category in this research: Organizational Management. The work organization points out mainly the necessity to accomplish the rules and the regulations of the enterprise, hiearchic stiffness and control, difficulties in accomplishing the prescribed work. On what concerns the working conditions, there is a difference in the satisfaction level between the two groups. While the majority of the business workers showed themselves satisfied in relation to illumination, noise, temperature and ventilation, hygiene, machinery and equipment; some operational workers demonstrated a certain amount of insatisfaction on what concerns the same topics presented before. The work relations established were defined as good and satisfactory by the components of both groups. The experiences of pleasure and suffering and the strategies of coping also compose another big category named as the subjective mobilizacion related to work. We noticed some satisfaction and pride in the participants for working in such an enterprise as a famous shopping center. The workers consider that their work provides the conquest of some of their objectives, such as their family living conditions and it is also a daily learning process. Another pleasure indicator was pointed out by the workers: the acknowledgement of their effort by the enterprise, their bosses, co-workers, family, and the public in general. The routine is tiresome for many of them. There were accounts of insatisfaction in relation to working on weekends and holidays. The strategies of coping used indicate the denial and/or rationalization in the form of: resignation, submission and/or acceptance, especially in relation with the work organization and the working conditions.